PRINSIP KARAKTERISTIK HADITS DALAM ENTERPRENEURSHIP - Hidayat, Hamdi; Tidjani, Ahmad Fauzi (Universitas Muhammadiyah Makassar, 2024)
This research aims to examine the principles of entrepreneurship from the perspective of hadith, which provide ethical guidance for Muslim entrepreneurs in managing their businesses. The analyzed hadiths emphasize essential values such as honesty (siddiq), trustworthiness (amanah), intelligence (fathonah), and the ability to convey goodness (tabligh) as fundamental characteristics that an entrepreneur must possess. These values not only guide the pursuit of material gain but also seek blessings and the pleasure of Allah. Through a qualitative approach using literature review methods, this study finds that entrepreneurship based on hadith teachings significantly contributes to building a sustainable and balanced economy. Muslim entrepreneurs are expected to practice noble business ethics, focusing on integrity, responsibility, and social engagement. Moreover, the study shows that entrepreneurship in Islam not only plays a role in improving individual economic well-being but also contributes to the welfare of society at large. Thus, these hadiths offer spiritual and moral guidance that remains relevant for modern-day entrepreneurs.